ثریا شہاب کی شاعری : احساس، لہجے اور جذبے کا جامع و تنقیدی مطالعہ: A Comprehensive and Critical Study of Suraiya Shahab’s Poetry with Respect to Feeling, Tone, and Emotional Expression (Al-Aasar, 2025)
This study offers a comprehensive and critical overview of Suraiya Shahab’s poetry, highlighting the emotional, thematic, and stylistic dimensions that define her creative identity. Although widely recognized as a dignified broadcaster and an informed journalist, the most subtle and aesthetically rich aspect of Shahab’s personality emerges through her poetry. Her work reveals an inner world shaped by emotional sensitivity, aesthetic refinement and an intimate engagement with personal experience. Shahab’s poetry is marked by the authenticity of feeling, depth of tone, and layered emotional resonance. Themes such as migration, loneliness, existential displacement, feminine consciousness, and the delicate aesthetics of love form the core of her poetic expression.  Critically, Shahab’s poetry stands out for its soft yet profound emotional landscapes, its internal dialogues, and its quiet musicality. While her work has not received the scholarly attention it deserves, it holds significant potential for future academic exploration, particularly in the domains of feminist poetics, diasporic literature, sound aesthetics, and modern Urdu poetic expression. Suraiya Shahab’s poetry, therefore, represents a delicate yet enduring contribution to Urdu literature—intimate, reflective, emotionally resonant and deeply human. Her depiction of love remains subtle, atmospheric, and emotionally textured, often expressed through natural imagery such as rain, seasons, and quiet remembrance.